The Immunomodulatory Properties of the Human Amnion-Derived Mesenchymal Stromal/Stem Cells Are Induced by INF-γ Produced by Activated Lymphomonocytes and Are Mediated by Cell-To-Cell Contact and Soluble Factors - Bulati, Matteo; Miceli, Vitale; Gallo, Alessia; Amico, Giandomenico; Carcione, Claudia; Pampalone, Mariangela; Conaldi, Pier Giulio (Frontiers in Immunology, 2020)
Human mesenchymal stromal cells (MSCs) represent the prototype cells in regenerative medicine, and are the most widely studied cell type in both preclinical and clinical trials. It has been demonstrated that MSCs directly affect immune cell response by expressing soluble immunosuppressive factors such as IDO, PGE2 and IL-10. MSCs also release exosomes able to give different effects, in a paracrine manner, by influencing inflammatory processes. The effects of MSCs on immune responses are suggested by their direct interaction with almost all the cells of the immune system. In this study, we aimed to establish the potential role of human amnion-derived MSCs (hAMSCs), in immunomodulation. We found that the immunosuppressive properties of hAMSCs are not constitutive, but require “supportive signals” capable of promoting these properties. Indeed, we found that hAMSCs alone are not able to produce an adequate amount of soluble immunomodulatory factors. Here we studied, in depth, the strong immunomodulatory licensing signal deriving from the direct interaction between hAMSCs and stimulated peripheral blood mononuclear cells. We found that the immunomodulatory effect of hAMSCs also depends on cell-to-cell contact through the contribution of the PDL-1/PD-1 axis. We then investigated the IFN-γ priming of hAMSCs (γ-hAMSCs), which induce the increase of PDL-1 expression, high production of IDO, and upregulation of different immunomodulatory exosome-derived miRNAs. Our miRNA-target network analysis revealed that 9 of the deregulated miRNAs are involved in the regulation of key proteins that control both T cell activation/anergy and monocyte differentiation pathways. Finally, we observed that γ-hAMSCs induce in monocytes both M2-like phenotype and the increase of IL-10 production. The extensive implications of MSCs in modulating different aspects of the immune system make these cells attractive candidates to be employed in therapeutic application in immune-based diseases. For these reasons, we aimed, with this study, to shed light on the potential of hAMSCs, and how they could become a useful tool for treating different inflammatory diseases, including end-stage pathologies or adverse effects in transplanted patients.